Are state telemedicine parity laws associated with greater use of telemedicine in the emergency department?. Issue 1 (14th January 2021) - Zachrison, Kori S.; Boggs, Krislyn M.; Cash, Rebecca E.; Burton, Kyle R.; Espinola, Janice A.; Hayden, Emily M.; Sauser, Joseph P.; Mehrotra, Ateev; Camargo, Carlos A.
Abstract: Background: Telemedicine is a valuable tool to improve access to specialty care in emergency departments (EDs), and states have passed telemedicine parity laws requiring insurers to reimburse for telemedicine visits. Our objective was to determine if there is an association between such laws and the use of telemedicine in an ED. Methods: As part of the 2016 and 2017 National ED Inventory–USA surveys, directors of all 5404 EDs in the United States were surveyed on the use of telemedicine. States were divided into those with any form of telemedicine parity law and those without (as of January 2016). We investigated the association between a telemedicine parity law and the use of telemedicine controlling for ED characteristics; state was included as a random intercept. Results: In 2016, among the 50 states and the District of Columbia (DC), 21 (41%) had a telemedicine parity law, whereas 30 (59%) did not. Among the 4418 ED respondents to the telemedicine question (82% response rate), 2352 (53%) received telemedicine. The proportion of EDs receiving telemedicine varied widely across the states and DC, ranging from 13% in DC to 89% in Maine. Neither the presence nor duration of state telemedicine parity laws were independently associated with ED receipt of telemedicine in 2016 nor the adoption of telemedicine from 2016 to 2017. Conclusion: Telemedicine parity laws were not associated with use of telemedicine in the ED. These results suggest that other factors are driving the wide variation in ED use of telemedicine across states.